Optimization techniques for crop planning: A review - JAIN, RAJNI; MALANGMEIH, L; RAJU, S S; SRIVASTAVA, S K; IMMANEULRAJ, KINGSLY; KAUR, AMRIT PAL (The Indian Journal of Agricultural Sciences, 2018)
The paper critically reviews various methods exclusively used for crop planning and points out suggestions for improvement in techniques used for crop planning. Specifically, the study examines scope for optimization of crop plan, objectives and constraints, approaches, seasonality issues, sensitivity analysis and various computer software packages used in computing the optimum models. With such extensive coverage, it intends to help the end users to decide upon an appropriate/suitable method corresponding to their situation and scenarios to frame the best and most practical/realistic optimum crop model. The paper also lists many model management options for developing such models. Finally, the paper presents a brief case study of Punjab state to illustrate an improvement in the methodological approach especially pertaining to aspects of sustainability, food security and seasonality in crop cultivation.